Dual energy CT angiography in peripheral arterial stents: optimal scanning protocols with regard to image quality and radiation dose - Almutairi, Abdulrahman; Al Safran, Z.; AlZaabi, S.; Sun, Zhonghua (AME Publishing Company, 2017)
Background: To determine the optimal scanning protocols of dual energy computed tomography angiography (DECTA) in terms of radiation dose and image quality assessment at different keV levels, and compare it with conventional computed tomography angiography (CTA) in patients treated with peripheral arterial stents. Methods: Twenty-nine patients with previous stent placement in peripheral arteries were evaluated with DECTA. Images were reconstructed with virtual monochromatic spectral imaging (VMS) at 65, 68, 70 and 72 keV and adaptive statistical iterative reconstruction (ASIR) at 50% compared with CTA. Image quality comprising image noise, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were assessed, and radiation dose was compared. Effects of different type of peripheral arterial stents on image quality were also evaluated. Fifty-six uniquely identified stents that were located in common iliac arteries (CIA), external iliac arteries (EIA) and superficial femoral arteries (SFA) were evaluated. Results: Within subjects, the results showed that DECTA images (VMS) had less noise than the CTA images for CIA, EIA and SFA stents, with the lowest noise at 72 keV. Also, the VMS images had greater SNR than the CTA images for the EIA stents (P<0.05); and the VMS images had greater CNR than the CTA images for CIA, EIA, and SFA stents (P<0.001). Also, on CT attenuation, VMS continued to outperform CTA, but to a lesser extent. Between subjects, average VMS noise varied significantly with the type of the stent used (P=0.025) for CIA stents. Radiation dose was highly significant between DECTA and conventional CTA scans (6.98 vs. 7.40 mSv, P=0.047). Conclusions: We conclude that an optimal scanning protocol consisting of 72 keV and 50% ASIR leads to better image quality for DECTA in peripheral arterial stenting when compared to conventional CTA.